Influence of deviation tolerances on the positioning accuracy using computer aided dynamic navigation in endodontic surgery: a proof-of-concept - Si-Min Liu; Li Peng; Yi-Jiao Zhao; Bing Han; Xiao-Yan Wang; Zu-Hua Wang (Head & Face Medicine)
Abstract Background The operation accuracy of dynamic navigation is affected by deviation tolerance settings. This in vitro study was aimed to assess the influence of distance and angle deviation tolerances (DDT and ADT) on positioning accuracy in endodontic surgery using dynamic navigation. Materials and methods Standardized models were designed and three-dimensional (3D) printed. The drilling depth was 15 mm, where hemispherical cavities were reserved. According to the DDTs and ADTs, they were divided into five groups (n = 10), and the tolerances of distance/angle deviation were set at 0.3 mm/5°, 0.6 mm/3°, 0.6 mm/5°, 0.6 mm/7°, and 0.9 mm/5°. During navigation guidance, the operation was completed from the model surface to the cavity, the trajectory of the approach was fitted and compared with the design path, and the operational accuracy was calculated and analyzed using one-way ANOVA. Results When the ADT was 5°, the positioning two-dimensional (2D) distance deviation of the DDT 0.3 mm group and the 0.6 mm group were 0.52 ± 0.14 mm and 0.50 ± 0.07 mm, respectively, smaller than 0.73 ± 0.17 mm of the 0.9 mm group (P <.01). The positioning 3D distance deviation of the 0.3 mm group and the 0.6 mm group were 0.55 ± 0.15 mm and 0.53 ± 0.07 mm, respectively, smaller than 0.74 ± 0.17 mm of the 0.9 mm group (P <.01). When the DDT was set as 0.6 mm, the positioning angle deviation of the ADT 3° group and the 5° group were 2.21 ± 0.42° and 2.60 ± 0.59°, respectively, smaller than 4.72 ± 0.64° of the 7° group (P <.01). Conclusion A 0.6 mm DDT and 5° ADT can reduce the positioning deviation of dynamic navigation and obtain better operability. The deviation tolerance of 0.6 mm/5° is suggested for application of dynamic navigation in endodontic surgery. It might improve the operation efficiency and ensure positioning accuracy.